2003
DOI: 10.1063/1.1608493
|View full text |Cite
|
Sign up to set email alerts
|

Study of a single dangling bond at the SiO2/Si interface in deep submicron metal–oxide–semiconductor transistors

Abstract: Two-level charge pumping (CP) measurements have been used for the study of a single trap situated at the SiO2/Si interface of sub-100 nm metal–oxide–semiconductor transistors (50 nm length). At room temperature, we have measured the emission time constant (τ) of the single trap and verified that the generation-recombination process was consistent with the Shockley–Read–Hall theory. Temperature-dependent CP measurements have been used to determine the thermal variation of the emission time constant. We show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…4. It has been reported that I CPMAX ≤fq for a single trap [4]- [7]. However, we successfully observed cases of I CPMAX =2fq as shown in Fig.…”
Section: Resultsmentioning
confidence: 53%
“…4. It has been reported that I CPMAX ≤fq for a single trap [4]- [7]. However, we successfully observed cases of I CPMAX =2fq as shown in Fig.…”
Section: Resultsmentioning
confidence: 53%
“…In this method, we apply ac bias to the gate, just like we do in the metal-based turnstile, and measure the interface-defect mediated current flowing between the two terminals (one usually the source and the other the substrate) for conventional bulk MOS transistors. Several studies followed [31][32][33][34], and surprisingly, they all were done at room temperature or even above it, showing the power of the charge-transfer scheme employing natural defects. By reducing the size of the transistor, N is expected to finally reach unity, and the single-charge transfer synchronized with the gate clock can be realized.…”
Section: Single-charge Transfer Via Dopant Atomsmentioning
confidence: 99%
“…We will need a cross section comparable to or larger than the values for the interface defects, which is on the order of 10 -16 -10 -17 cm 2 or larger [32][33][34]36]. First, the dopant must have a large capture cross section both for electrons in the conduction band and for holes in the valence band.…”
Section: Single-charge Transfer Via Dopant Atomsmentioning
confidence: 99%
“…The observation of single traps at the interface has been demonstrated by the CP method using submicron MOSFETs [2][3], and the trap capture cross sections for electrons and holes have been derived for particular traps [4]. Moreover, the capture cross sections for electrons and holes, and the energy level of particular interface traps have been examined by utilizing the three-voltage level CP method [5] using deep-submicron MOSFETs [6][7].…”
Section: Introductionmentioning
confidence: 99%